Principal Management in Implementing Multiculturalism Religious Ulturalism on Tolerance Development in Junior High School (SMP) at Surabaya - Fais, Ahmad; Wulandari, Ayu; Amalia, Kaniati (Universitas Muhammadiyah Gorontalo, 2025)
Religious and ethnic diversity will give birth to problems, disputes and disharmony in the community and in the school environment. Based on this, in YPPI-1 and Dharma Wanita Junior High School (SMP), there is still a sense of wanting to discriminate in the midst of ethnic and religious differences and frequent disputes between students with one another. This research aims to find out how the principal's management in implementing religious multiculturalism in developing tolerance so that the problems of differences that occur can provide solutions and find out the supporting and inhibiting factors in the management process at school. This research is a qualitative research, data collection is done by observation, interview and documentation. As respondents in this study, researchers used several informants such as: principals, teachers, and several students with different religious backgrounds. Then in analyzing the data, researchers used data reduction, data display and data verification. Then to get data validity using the data triangulation method. The results of this study describe the principal's management in implementing religious multiculturalism in developing tolerance at YPPI-1 Junior High School and Dharma Wanita Junior High School in order to continue to optimize the realm of planning, organizing, implementing and supervising by school components by taking into account the needs and situations that exist, by prioritizing and considering elements of justice and togetherness. Supporting factors of the principal's management are teachers, school activity programs and interactions between components at school, inhibiting factors include ethnic background, family, and media viewing.